Evaluating Single Spacecraft Observations of Planetary Magnetotails With Simple Monte Carlo Simulations: 2. Magnetic Flux Rope Signature Selection Effects. Issue 12 (22nd December 2018) - Smith, A. W.; Jackman, C. M.; Frohmaier, C. M.; Fear, R. C.; Slavin, J. A.; Coxon, J. C.
Abstract: A Monte Carlo method of investigating the effects of placing selection criteria on the magnetic signature of in situ encounters with flux ropes is presented. The technique is applied to two recent flux rope surveys of MESSENGER data within the Hermean magnetotail. It is found that the different criteria placed upon the signatures will preferentially identify slightly different subsets of the underlying population. Quantifying the selection biases first allows the distributions of flux rope parameters to be corrected, allowing a more accurate estimation of the intrinsic distributions. This is shown with regard to the distribution of flux rope radii observed. When accounting for the selection criteria, the mean radius of Hermean magnetotail quasi‐force‐free flux ropes is found to be 58 9 − 269 + 273  km. Second, it is possible to weight the known identifications in order to determine a rate of recurrence that accounts for the presence of the structures that will not be identified. In the case of the Hermean magnetotail, the average rate of quasi‐force‐free flux ropes is found to 0.12 min −1 when selection effects are accounted for (up from 0.05 min −1 previously inferred from observations). Key Points: A Monte Carlo method is presented to estimate and correct for sampling biases in spacecraft surveys of magnetic flux ropes Method allows the correction of observed distributions (e.g., flux rope radii) according to the selection criteria employed Accounting for unidentified flux ropes increases the average rate of flux ropes in Mercury's magnetotail from 0.05 to 0.12 min −1